Electronic banking services their means and jurisprudential rulings - Mohammed, Abdellatif Elkhayali (Journal of Islamic Sciences, 2024)
The research aims to define electronic banking services, which have become essential in our lives, and to know their means and jurisprudential rulings. The researcher adopted the historical methodology and descriptive-analytical in this research, which belongs to the field of Sharia sciences related to the jurisprudence of electronic banking transactions. He divided it into three sections: the first section dealt with electronic banking in terms of origin, concept, advantages, and means, while the second section identified credit cards, and the third section was devoted to the jurisprudence ruling of some electronic banking services. Among the results of this research, electronic banking services are the services provided by banks based on electronic means, including credit cards. Sharia boards have authorized these services that were compatible with the rulings of Sharia and do not include a Sharia prohibition.